Resident Duty Hour Compliance and Sleep after Transitioning to a Night Float System: A Prospective Observational Study in an Academic Urology Program. Issue 3 (11th May 2021) - Mohapatra, Anand; Bandari, Jathin; Orikogbo, Oluwaseun; Macleod, Liam C.; Jackman, Stephen V.; Davies, Benjamin J.; Jacobs, Bruce L.
Abstract: Introduction: Our urology residency program transitioned to a night float system, where dedicated residents cover nights and are off duty during the day. Junior residents previously covered 5 hospitals every 5 to 7 nights and worked the following day (home call). This prospective observational study compared the 2 systems before and after the transition. Methods: A validated survey was administered to residents and faculty to evaluate patient care, communication, quality of life, resident education, and duty hour violations. A separate survey was administered to nurses evaluating the on-call resident. Sleep was measured using actigraphy. Results: Survey response rates were 80% to 100%. Junior residents rated night float as equivalent to home call for surgical case volume and superior in all other respects (p <0.05). Senior residents rated night float as superior for continuity of care, compassion, safety, efficiency for the day team, communication with nurses, quality of life, and time for reading and research (p <0.05). Faculty rated night float as superior for efficiency for the day team, handoffs, quality of life, and time for research (p <0.05). Nurses rated night float higher for availability, knowledge of plan for patient, respectfulness, communication, and ability to identify the resident on call (p <0.05). Mean duration of sleep was 2.5 and 7.1 hours for home call and night float, respectively (p <0.001). Junior residents reported fewer violations of the 80-hour and 8-hour-off rules with night float (p <0.001). Conclusions: Physicians and nurses perceived night float to improve multiple domains. Residents slept more and had fewer duty hour violations on night float.